Reveiw of Developed Object Detection Techniques for Auto Detection System - Singh, Anita; Kumar, Rajesh; Tripathi, R. P. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*332.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90074);" role="presentation">The automatic detection has emerged as a technique in a realis<span dir="ltr" style="left: calc(var(--scale-factor)*324.67px); top: calc(var(--scale-factor)*332.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951184);" role="presentation">tic manner within the field of a<span dir="ltr" style="left: calc(var(--scale-factor)*450.22px); top: calc(var(--scale-factor)*332.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935776);" role="presentation">utomation. This is <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*345.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897855);" role="presentation">very use<span dir="ltr" style="left: calc(var(--scale-factor)*105.98px); top: calc(var(--scale-factor)*345.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946805);" role="presentation">ful in defence as well as civil <span dir="ltr" style="left: calc(var(--scale-factor)*227.45px); top: calc(var(--scale-factor)*345.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897588);" role="presentation">sector. <span dir="ltr" style="left: calc(var(--scale-factor)*256.73px); top: calc(var(--scale-factor)*345.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919991);" role="presentation">The main objective of the paper is to model, simulate and ana<span dir="ltr" style="left: calc(var(--scale-factor)*507.22px); top: calc(var(--scale-factor)*345.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906579);" role="presentation">lyse <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*359.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925437);" role="presentation">Automatic Target Detection and Shooting (ATDS) of objects, used for target acquisition, tracking, detection and <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*372.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897162);" role="presentation">shooting. The proposed paper can be divided <span dir="ltr" style="left: calc(var(--scale-factor)*254.21px); top: calc(var(--scale-factor)*372.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93449);" role="presentation">into the following techniques:  <span dir="ltr" style="left: calc(var(--scale-factor)*108.02px); top: calc(var(--scale-factor)*399.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928562);" role="presentation">Improvised parametric ratios algorithm for blob analysis of obj<span dir="ltr" style="left: calc(var(--scale-factor)*360.43px); top: calc(var(--scale-factor)*399.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915506);" role="presentation">ect recognition.  <span dir="ltr" style="left: calc(var(--scale-factor)*108.02px); top: calc(var(--scale-factor)*413.47px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904605);" role="presentation">Feature based target classification algorithm.  <span dir="ltr" style="left: calc(var(--scale-factor)*108.02px); top: calc(var(--scale-factor)*426.67px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919433);" role="presentation">Analysis of different data samples for classification by Bag of feature technique.  <span dir="ltr" style="left: calc(var(--scale-factor)*108.02px); top: calc(var(--scale-factor)*439.99px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93357);" role="presentation">Algorithm for imprecise test detector, HOG-<span dir="ltr" style="left: calc(var(--scale-factor)*286.25px); top: calc(var(--scale-factor)*439.99px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931159);" role="presentation">SVM classifier technique. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*466.39px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919399);" role="presentation">This system has the ability to classify <span dir="ltr" style="left: calc(var(--scale-factor)*224.81px); top: calc(var(--scale-factor)*466.39px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925129);" role="presentation">the physically existing objects like tank, jeep, tetra truck in real time using <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*479.59px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920952);" role="presentation">thermal imaging cameras during night time as well as in bad weather conditions<span dir="ltr" style="left: calc(var(--scale-factor)*395.23px); top: calc(var(--scale-factor)*479.59px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9179);" role="presentation">. The <span dir="ltr" style="left: calc(var(--scale-factor)*418.99px); top: calc(var(--scale-factor)*479.59px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931613);" role="presentation">Analysis of all techniques <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*492.79px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923099);" role="presentation">are provided in tabular form